Factores atribuibles a ruptura prematura de membranas en gestantes atendidas en el hospital Iquitos César Garayar García 2020- 2022 - Cusacani Marca, Alan Nilwar (2024)
Premature rupture of the membrane occurs in around 10% of deliveries in our country, it predisposes complications in the mother and the fetus, such as infections in the mother and newborn, prematurity, respiratory distress syndrome, neurological sequelae, and intrauterine death; Although the pathophysiology is not yet well defined, it has been associated with maternal factors, the present study has the purpose of identifying the factors with the greatest attribution to the presence of premature membrane rupture, for which an analytical study of control case, comparing 181 pregnant women with premature rupture of the membrane and 362 pregnant women without its presence, determining the association between the study variables through the odds ratio, and its significance through the non-parametric chi-square test.